Endless Accumulation, Limits to Growth, and the Tendency for the Rate of Profit to Fall. (1st July 2016) - ,
Abstract : This article proposes a simple new model that helps to analyze the long-term movement of the profit rate. The article applies the new model to the United States and China, the world's two largest economies, to illustrate how the new model may help analyze the global capitalist crisis in the 21st century. In the new model, the long-term movement of the profit rate depends on the long-term average economic growth rate and the ratio of accumulation. As the capitalist economy stagnates and ecological sustainability imposes constraints on future economic growth, capitalism may have exhausted its historical capacity to check the tendency for the rate of profit to fall.